(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article discusses significant changes in American children’s literature the 20th century, with the rise and development of a variety of genres that are now essential to the canon of books for young readers. This study explores the unique characteristics, noteworthy accomplishments, and long-lasting influence of the mystery, fantasy, and realism genres on children’s literature